Therapeutic Potential of TACE Inhibitors in Stroke - Lovering, F.; Zhang, Y. (Current Drug Targets-CNS & Neurological Disorders, 2005)
Stroke is the third leading cause of death and the leading cause of permanent disability in western countries and the incidence of stroke is expected to increase in the foreseeable future due to the ageing population. The effective treatment of stroke remains challenging due to the complexity and heterogenicity of the disease. Recombinant tissue plasminogen activator (rt-PA) is the only FDA-αpproved therapy for stroke during the first 3 hr after the disease onset. However the risk of hemorrhage and its narrow therapeutic window has limited its use in clinic. Inflammation has been known to play a crucial role in the induction and development of stroke and tumor necrosis factor-α (TNF-α) is a central player in the initiation of multiple inflammatory cascades. The recent success of three anti-TNF biologics in the clinic for the treatment of rheumatoid arthritis as well as other inflammatory diseases has further validated TNF159nflammation. TNF-α has also been shown to be associated with ischemic stroke. Anti-TNF biologics have been shown to be effective in reducing the disease symptoms in various pre-clinical stroke models. Small molecule TNF inhibitors are highly desirable due to the limitations of protein therapeutics. Tumor necrosis factor-alpha-converting enzyme (TACE) is the major sheddase of TNF-α and is essential for the generation of soluble, mature TNF-α. Thus TACE appears to be an attractive target for development of oral small molecule TNF-α inhibitors. This review summarizes the role of TNF-α in stroke and the effect of several TACE/MMP inhibitors in pre-clinical stroke models. The data strongly suggest that TACE/MMP inhibitors have great therapeutic potential and may be valuable alternatives in treating stroke in the clinic.
Keywords: tnf